Kidults culture in Singapore. - Huang, Esther Xinhuang. (2008)
Includes Appendices: 1 Feature Writing Book-- 1 Feature Writing. Our final year project aims to inform Singaporeans on the growing kidult phenomenon in Singapore. Actually, kidults are not new, as can be seen from how people have collected dolls since a long time ago, but few people are aware of it. The term “kidult’’ was first coined by New York Times journalist Peter Martin in 1985, to describe adults who enjoy being a part of youth culture, retain and display certain elements of childlikeness.